Pelaksanaan Analisis Jabatan Tepat dalam Rangka Meningkatkan Efektivitas Kerja (Studi Kasus Pada Bagian Organisasi Setda Kota Binjai) - Aisyah Fitri Pasaribu; Muhammad Irwan Padli Nasution (Universitas Muhammadiyah Enrekang, 2022)
Job analysis is very important in organizations to place people in a position / job according to their abilities. However, in reality there are organizations that feel that there is no need to bother making job descriptions and job specifications because they assume that all employees will know what to do later. The research method used by the researcher in this research is a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews and documentation studies. The results obtained by the researchers are that the implementation of proper job analysis can increase the effectiveness of employees' work at the Binjai Mayor's office.